Electrolyte containing metal ion indicator as well as preparation method and application of electrolyte

By using metal ion indicators as electrolyte additives in water-based energy storage devices, problems such as corrosion of zinc dendrites and copper negative electrodes are solved, and high stability and versatile electrolytes are achieved, which significantly improves the performance and application potential of energy storage devices.

CN119725798AActive Publication Date: 2025-03-28SUN YAT SEN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510028620.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-28
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Water-based energy storage devices are prone to corrosion of zinc dendrites and copper negative electrodes during charging and discharging, which limits their high-performance applications. The existing additives have a single function and unstable structure, making it difficult to meet the needs of versatility and high stability.

Method used

Metal ion indicator is used as electrolyte additives, and the solvation structure of metal ions is adjusted by complexing with metal ions in the electrolyte, reducing side reactions and improving device performance. Metal ion indicators have a stable molecular structure, can maintain their functions during multiple charges and discharges, and participate in reversible redox reactions through functional groups such as hydroxyl and azo groups, thereby increasing the energy density of the battery.

Benefits of technology

It significantly improves the cycle life and energy density of zinc negative electrodes, reduces the occurrence of electrode side reactions, improves the overall performance of the battery, and provides a detection method for electrolyte structure changes through color change characteristics, improving the application prospects of electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725798A_ABST
    Figure CN119725798A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte containing a metal ion indicator as well as a preparation method and application of the electrolyte. The metal ion indicator is an organic compound or a salt thereof; the organic compound has a parent nucleus structure and a substituent group, and the parent nucleus structure is 4-dibenzylidene-2, 5-cyclohexadiene-1-ketone, phenylazonaphthalene, triazinyl phenylazonaphthalene, naphthyl azonaphthalene, diphenyl bisazonaphthalene, phenylazobenzene or triphenylmethane. According to the invention, the metal ion indicator is used as an electrolyte additive, so that not only can the color-changing characteristic be more convenient for characterization of boundary composition and structure, but also the solvation structure of the metal ions is improved after the metal indicator is combined with the metal ions, the side reaction of the electrode can be reduced, and the stability of the electrode is improved; and meanwhile, extra capacity is provided for the energy storage device through the reversible oxidation-reduction reaction, so that the application of the metal ion indicator as an additive in the electrolyte provides new possibility for the design of the energy storage device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to an electrolyte containing a metal ion indicator and a preparation method and application thereof. Background Art

[0002] In today's society, with the continuous development of renewable energy technology, the demand for energy storage devices is increasing. The rapid popularization of electric vehicles, smart grids and large-scale energy storage systems has made efficient and safe energy storage technology a hot topic of research. Although traditional lithium-ion batteries have excellent performance in energy density and cycle life, they have gradually revealed their limitations due to the poor safety and environmental pollution of the organic electrolytes they use. In contrast, aqueous energy storage devices have become an important direction for future energy storage technology with their advantages of low cost, environmental friendliness and high safety. Aqueous electrolytes not only have good conductivity and thermal stability, but also provide the possibility of achieving higher energy density in battery design and application. However, aqueous energy storage devices still face many challenges. For example, zinc dendrites are easily formed on the zinc negative electrode during charging and discharging, which not only affects the performance of the battery, but also may cause safety hazards; and copper negative electrodes are also prone to corrosion and uneven deposition in the electrolyte. These problems limit the application of aqueous electrolytes in high-performance energy storage devices, and it is urgent to improve the overall performance of the battery through new materials and new technologies.

[0003] In the regulation of aqueous electrolytes, the introduction of organic molecules is regarded as an effective strategy. Organic additives can improve the performance of batteries by changing the chemical and physical properties of electrolytes. For example, additives can inhibit the formation of zinc dendrites by adjusting the solvation structure and optimizing the solvation environment of zinc ions. In addition, adjusting the pH value of the electrolyte can also effectively improve the stability of the electrode and reduce the problems of corrosion and uneven deposition. However, there are also some problems in the current research on additives, mainly manifested in single function and unstable structure. Many additives may degrade or lose their effectiveness under certain conditions, which limits their practical applications. Therefore, the development of electrolytes with multifunctionality and high stability is crucial to improving the overall performance of aqueous electrochemical energy storage. Researchers are in urgent need of exploring new additives to improve their application effects in electrolytes by optimizing their molecular structure and function. Summary of the invention

[0004] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide an electrolyte containing a metal ion indicator. The second purpose of the present invention is to provide an aqueous electrochemical energy storage device. The third purpose of the present invention is to provide an application of the aqueous electrochemical energy storage device.

[0005] Metal ion indicators are mainly used in the field of titration, and their color change principle and complexing ability with metal ions have attracted much attention. These indicators usually contain ring structures with delocalized electrons such as benzene, naphthalene, pyridine or triphenylmethane. These ring structures not only give the indicators good optical properties, but also improve their chemical stability and selectivity. In order to enhance the complexing ability with metal ions, these indicators often also contain functional groups with lone pairs of electrons such as hydroxyl, sulfonic acid, carboxyl, azo and halogen. These functional groups can form strong coordination interactions with metal ions. When metal ions are present, the indicator will complex with the metal ions, and when the metal ions combine with the indicator, the new compound formed has different electronic structure and optical properties. This structural change will lead to changes in the absorption spectrum, so the color changes significantly, which enables it to be used to monitor the concentration of metal ions in real time. By adjusting the type and position of these functional groups, researchers can design metal ion indicators with specific functions to meet different application requirements.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides an electrolyte containing a metal ion indicator, wherein the metal ion indicator is an organic compound or a salt thereof; the organic compound has a parent core structure and a substituent, and the parent core structure is selected from 4-dibenzhydryl-2,5-cyclohexadiene-1-one, phenylazonaphthalene, triazine-phenylazonaphthalene, naphthylazonaphthalene, diphenylbisazonaphthalene, phenylazobenzene, benzene or triphenylmethane; the substituent of the organic compound is selected from at least one of a hydroxyl group, a sulfonic acid group, a carboxyl group, a halogen group, an arsenic acid group, and a dicarboxymethyl nitrogen group.

[0008] The present invention uses a metal ion indicator as an electrolyte additive. After the metal ion indicator is complexed with the metal ions in the electrolyte, it can effectively adjust the solvation structure of the metal ions, thereby reducing the occurrence of side reactions and improving device performance, and has great application potential in the field of aqueous energy storage devices. Compared with traditional additives, the molecular structure of metal ion indicators is generally more stable and can maintain its function during multiple charge and discharge processes. In addition, when these indicators complex metal ions, they can often adjust the pH value of the electrolyte to avoid corrosion problems caused by acid-base imbalance. More importantly, due to the participation of functional groups such as hydroxyl and azo groups, these indicators can undergo reversible redox reactions, thereby increasing the energy density of the battery. This feature not only enhances the performance of the battery, but also helps improve its cycle life.

[0009] At the same time, metal ion indicators have the characteristic of changing color after complexing with metal ions. By observing the color change and using color-sensitive test methods, such as UV-visible absorption spectroscopy, it is possible to further detect changes in the electrolyte structure and analyze its change mechanism, providing a systematic strategy for electrolyte analysis and design. Therefore, metal ion indicators have broad application prospects in aqueous electrolytes.

[0010] The term "salt" refers to salts of the compounds of the present invention, prepared from the compounds having specific substituents discovered in the present invention and relatively non-toxic acids or bases. Electrochemically acceptable salts are preferred.

[0011] Preferably, when the core structure is 4-dibenzhydryl-2,5-cyclohexadiene-1-one, the metal ion indicator is pyrogallol purple, meta-cresol purple, meta-cresol purple sodium, xylenol orange sodium, methylthymol blue, bromocresol purple, bromocresol purple sodium, bromocresol green, or bromocresol green sodium. The information of the above organic compounds is shown in Table 1:

[0012] Table 1 Metal ion indicators with a core structure selected from 4-benzhydryl-2,5-cyclohexadiene-1-one

[0013]

[0014]

[0015] Preferably, when the parent core structure is phenylazonaphthalene, the metal ion indicator is acidic mordant blue K, 1-(2-pyridyl azo)-2-naphthol, chrome blue SE. The information of the above organic compounds is shown in Table 2:

[0016] Table 2 Metal ion indicators whose parent core structure is selected from phenylazonaphthalene

[0017]

[0018] Preferably, when the parent core structure is triazine phenyl azonaphthalene, the metal ion indicator is Reactive Red 2. The information of the above organic compounds is shown in Table 3:

[0019] Table 3 Metal ion indicators whose parent core structure is selected from triazine phenyl azonaphthalene

[0020]

[0021] Preferably, when the parent core structure is naphthyl azonaphthalene, the metal ion indicator is chrome black T or chrome blue black R. The information of the above organic compounds is shown in Table 4:

[0022] Table 4 Metal ion indicators whose parent core structure is selected from naphthyl azonaphthalene

[0023]

[0024] Preferably, when the parent core structure is diphenylbis(azo)naphthalene, the metal ion indicator is arsenazo III. The information of the above organic compounds is shown in Table 5:

[0025] Table 5 Metal ion indicators whose parent core structure is selected from diphenylbis(azo)naphthalene

[0026]

[0027] Preferably, when the parent core structure is phenylazobenzene, the metal ion indicator is 4-(2-pyridyl azo) resorcinol. The information of the above organic compounds is shown in Table 6:

[0028] Table 6 Metal ion indicators whose core structure is selected from phenylazobenzene

[0029]

[0030] Preferably, when the parent core structure is triphenylmethane, the metal ion indicator is bromophenol blue, bromophenol blue sodium, bromophenol red, bromophenol red sodium. The information of the above organic compounds is shown in Table 7:

[0031] Table 7 Metal ion indicators whose core structure is selected from triphenylmethane

[0032]

[0033] Preferably, the components of the electrolyte include: one or more of the metal ion indicators, a soluble electrolyte, and water.

[0034] More preferably, the soluble electrolyte includes at least one of zinc sulfate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, copper sulfate, copper chloride, magnesium chloride, calcium chloride, lithium chloride, sodium chloride, potassium chloride, and potassium hydroxide.

[0035] More preferably, the total concentration of the metal ion indicator in the electrolyte is 0.01 to 3000 mmol·L -1 More preferably, it is 0.1 to 50 mmol·L -1 More preferably, it is 1 to 10 mmol·L -1 .

[0036] More preferably, the concentration of the soluble electrolyte is 0.1 to 10 mol·L -1 More preferably, it is 1 to 3 mol·L -1 .

[0037] Preferably, the method for preparing the electrolyte containing the metal ion indicator comprises the following steps: mixing one or more of the metal ion indicators, a soluble electrolyte and water to prepare the electrolyte containing the metal ion indicator.

[0038] The second aspect of the present invention provides an aqueous electrochemical energy storage device, comprising a positive electrode, a negative electrode and the electrolyte containing the metal ion indicator described in the first aspect.

[0039] Preferably, the positive electrode is a positive electrode current collector loaded or unloaded with a positive electrode active material; the positive electrode active material is selected from at least one of activated carbon, carbon nanotubes, MXene, manganese-based oxides, vanadium-based oxides, Prussian blue derivatives, polyanion compounds, and organic positive electrode materials.

[0040] Preferably, the negative electrode is at least one of metallic zinc or metallic zinc-modified metal, metallic copper or metallic copper-modified metal, metallic tin or metallic tin-modified metal, metallic magnesium or metallic magnesium-modified metal, metallic calcium or metallic calcium-modified metal, metallic lithium or metallic lithium-modified metal, metallic potassium or metallic potassium-modified metal.

[0041] Preferably, the aqueous electrochemical energy storage device further comprises a diaphragm.

[0042] More preferably, the separator is selected from separator glass fiber, polyethylene, polypropylene polyolefin microporous membrane, porous polymer membrane, non-woven separator, filter paper or filter membrane.

[0043] The third aspect of the present invention provides any of the following applications of the aqueous electrochemical energy storage device described in the second aspect:

[0044] 1) Supercapacitors; 2) Hybrid capacitors; 3) Metal ion batteries; 4) Flow batteries.

[0045] Preferably, the aqueous electrochemical energy storage device is used in a Zn / / Zn symmetric battery.

[0046] Preferably, the aqueous electrochemical energy storage device is used in a Cu / / Cu symmetric battery.

[0047] Preferably, the aqueous electrochemical energy storage device is used in a Zn / / Cu asymmetric battery.

[0048] Preferably, the aqueous electrochemical energy storage device is used in a Zn / / AC zinc ion hybrid capacitor.

[0049] The beneficial effects of the present invention are:

[0050] (1) The present invention discloses an electrolyte containing a metal ion indicator. The metal ion indicator is used as an electrolyte additive. Not only can its color-changing characteristics facilitate the characterization of the boundary, composition and structure, but also after the metal indicator is combined with the metal ion, the solvation structure of the metal ion is improved, the occurrence of electrode side reactions can be reduced, and the electrode stability is improved. The Zn / / Zn symmetric battery using the BCPS color-changing electrolyte has a good stability at 25°C and 2 mA·cm -2 , 1mAh·cm -2 Under certain conditions, the cycle life can be increased from 33h without additives to 2000h. At the same time, its reversible redox reaction provides additional capacity for the energy storage device. Therefore, the application of metal ion indicators as additives in electrolytes provides new possibilities for the design of energy storage devices.

[0051] (2) The electrolyte containing the metal ion indicator of the present invention can be used as a new type of color-changing electrolyte. The present invention uses a metal ion indicator that can undergo a color change after combining with a metal ion. When the metal ion combines with the indicator, it will cause a redistribution of electrons. This change in energy level will cause the molecule's absorption characteristics of light to change, affecting the color of the solution, thereby causing a color change in the visible light region. The occurrence of the transformation can be directly observed by the naked eye, and the absorption spectrum changes due to the structural transformation. In related tests, the test results are more obvious, such as the UV-visible absorption spectrum. Therefore, the present invention takes color change as the design subject, provides a more direct electrolyte modification and characterization idea, and successfully applies the color-changing electrolyte to energy storage devices, promotes subsequent electrolyte research and development, and provides a new direction for the optimization of energy storage device design strategies and research paths in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 A color comparison diagram of the color-changing electrolytes prepared by different ion indicators in Example 1 (c in the figure), Example 2 (a in the figure), and Example 3 (b in the figure);

[0053] Figure 2 The UV-Vis spectra test chart and color comparison chart of the color-changing electrolyte with different molar ratios of BCPS and zinc sulfate and copper sulfate prepared in Example 1; wherein a is the UV-Vis spectrophotometry (UV-Vis) with the addition of zinc sulfate; b is the color change with the addition of zinc sulfate; c is the UV-Vis spectrophotometry (UV-Vis) with the addition of copper sulfate; d is the color change with the addition of copper sulfate;

[0054] Figure 3 The scanning electron microscope images of the metal zinc negative electrodes prepared in Example 1 (d in the figure), Example 2 (b in the figure), Example 3 (c in the figure) and Comparative Example 1 (a in the figure) after charge and discharge cycles;

[0055] Figure 4The Zn / / Zn symmetric cells prepared in Example 1 (d in the figure), Example 2 (b in the figure), Example 3 (c in the figure) and Comparative Example 1 (a in the figure) were heated to 25°C and the current density was 2 mA·cm -2 and 1mAh·cm -2 Time voltage curve under the conditions;

[0056] Figure 5 The Cu / / Cu symmetric cells prepared in Example 1 (b) and Comparative Example 1 (a) were heated to 25°C and 2 mA·cm -2 and 1mAh·cm -2 Time voltage curve under the conditions;

[0057] Figure 6 The charge and discharge coulombic efficiency (CE) diagram of the Zn / / Cu asymmetric battery prepared in Example 1 and Comparative Example 1;

[0058] Figure 7 CV test result diagram and redox reaction mechanism diagram of the Zn / / AC zinc ion hybrid capacitor prepared in Examples 1-2 and Comparative Example 1; wherein a is the CV test result diagram of Example 1; b is the CV test result diagram of Example 2; c is the redox reaction mechanism diagram;

[0059] Figure 8 The charge and discharge results of the Zn / / AC zinc ion hybrid capacitor prepared in Example 1 and Comparative Example 1 are shown;

[0060] Fig. 9 Schematic diagram of optimizing and regulating the color-changing electrolyte using the metal ion indicator prepared in Examples 1-3. DETAILED DESCRIPTION

[0061] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.

[0062] Example 1

[0063] This embodiment provides an electrolyte containing a metal ion indicator, and the preparation method thereof is as follows:

[0064] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 281.10 mg of bromocresol purple sodium (BCPS, 10 mmol / L -1 ) and used as a color-changing electrolyte for zinc negative electrode energy storage devices.

[0065] Example 2

[0066] This embodiment provides an electrolyte containing a metal ion indicator, and the preparation method thereof is as follows:

[0067] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 38.64 mg of pyrogallol purple (PV, 10 mmol·L -1 ) and used as a color-changing electrolyte for zinc negative electrode energy storage devices.

[0068] Example 3

[0069] This embodiment provides an electrolyte containing a metal ion indicator, and the preparation method thereof is as follows:

[0070] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 61.53 mg of Reactive Red 2 (RR, 10 mmol / L) was added. -1 ) and used as a color-changing electrolyte for zinc negative electrode energy storage devices.

[0071] Comparative Example 1

[0072] The comparative example provides an electrolyte solution without a metal ion indicator, and the preparation method thereof is as follows: 28753.00 mg of zinc sulfate heptahydrate is completely dissolved in 50 mL of deionized water at room temperature, and the solution is used as an electrolyte solution for a zinc negative electrode energy storage device.

[0073] Color change test

[0074] 1. Dissolve 0.19 mg of pyrogallol purple (PV) in 10 ml of deionized water at room temperature to prepare 0.05 mmol·L -1 Dissolve 0.31 mg of Reactive Red 2 (RR) in 10 ml of deionized water to prepare 0.05 mmol·L -1 Reactive Red 2 aqueous solution, set aside. Add two portions of 0.06 mg zinc sulfate heptahydrate (ZnSO4·7H2O, 0.05 mmol·L -1 ) were added with 4 ml of the above-prepared 0.05 mmol·L -1 In aqueous solution of pyrogallol violet and aqueous solution of reactive red 2.

[0075] Color changes such as Figure 1 For a and b in the figure, the solution color changed significantly after adding ZnSO4, indicating that PV and RR can undergo chelation and coordination with zinc ions.

[0076] At room temperature, dissolve 1.40 mg of bromocresol purple sodium in 50 ml of deionized water to prepare 0.05 mmol·L -1Bromocresol purple sodium aqueous solution, set aside. 0.06 mg zinc sulfate heptahydrate (ZnSO4·7H2O, 0.05 mmol·L -1 ), 0.03 mg copper sulfate (CuSO4, 0.05 mmol·L -1 ), 0.02 mg lithium chloride (LiCl, 0.05 mmol·L -1 ), 0.01 mg magnesium chloride (MgCl2, 0.05 mmol·L -1 ) add 4 ml of the above-prepared 0.05 mmol·L -1 Sodium bromocresol purple in aqueous solution.

[0077] Color changes such as Figure 1 As shown in Figure c, after adding ZnSO4, CuSO4, LiCl, and MgCl2 respectively, the BCPS solution underwent different degrees of color changes, indicating that BCPS was coordinated with metal ions.

[0078] 2. Add 0.01mg, 0.02mg, 0.03mg, 0.04mg, 0.06mg, 0.09mg and 0.11mg of zinc sulfate heptahydrate to 4ml of the above-prepared 0.05mmol·L -1 Sodium bromocresol purple in aqueous solution.

[0079] Color change and UV-Vis spectrophotometry (UV-Vis) test such as Figure 2 As shown in a and b, after adding different molar ratios of ZnSO4 to the BCPS solution, the color changed to varying degrees, and the hydroxyl peak near 427.5nm in the UV-Vis test showed an obvious red shift as the molar ratio of BCPS to ZnSO4 continued to increase, indicating that BCPS has a strong coordination effect with zinc ions and forms a relatively stable complex.

[0080] Add 0.006 mg, 0.01 mg, 0.02 mg, 0.025 mg, 0.03 mg, 0.05 mg, and 0.6 mg of copper sulfate to 4 ml of the 0.05 mmol / L -1 Sodium bromocresol purple in aqueous solution.

[0081] Color change and UV-Vis test Figure 2 As shown in c and d, after adding different molar ratios of CuSO4 to the BCPS solution, the color changed to varying degrees, and the hydroxyl peak near 427.5nm in the UV-Vis test showed an obvious red shift as the molar ratio of BCPS to CuSO4 continued to increase, and the conjugated structure peak at 588nm decreased significantly, indicating that BCPS also has a strong coordination effect with copper ions to form a relatively stable complex.

[0082] Electrochemical performance test

[0083] 1. Preparation of batteries and capacitors

[0084] The Zn / / Zn symmetric battery was assembled using zinc foil as positive and negative electrodes and filter paper as a separator. The Zn / / Cu asymmetric battery was assembled using copper foil as a positive electrode, zinc foil as a negative electrode and glass fiber as a separator. The Zn / / AC zinc ion hybrid capacitor was assembled using activated carbon as a positive electrode, zinc foil as a negative electrode and filter paper as a separator. The Cu / / Cu symmetric battery was assembled using copper foil as a positive and negative electrode and filter paper as a separator.

[0085] Preparation process of activated carbon (AC) positive electrode sheet: 800 mg of AC, 100 mg of conductive carbon black, and 100 mg of PVDF were weighed into an agate mortar according to the mass ratio of 8:1:1, and stirred evenly. Then 3 mL of NMP was dropped into the slurry and ground for 10 minutes until it became a uniform slurry. The slurry was evenly coated on the surface of the stainless steel sheet with an applicator, and then dried in a vacuum drying oven at 60°C for 12 hours, and then taken out and cut into positive electrode sheets with a diameter of 11.3 mm.

[0086] Preparation process of zinc electrode sheet: Use sandpaper to polish the surface of zinc foil, then cut it into negative electrode sheets with a diameter of 11.3 mm, add ethanol for ultrasonic cleaning, put it in an oven for drying, and take it out for use.

[0087] Preparation process of copper electrode sheet: polish the surface of copper-zinc foil with sandpaper, then cut it into negative electrode sheets with a diameter of 11.3 mm, add ethanol for ultrasonic cleaning, put it in an oven for drying, and take it out for use.

[0088] Glass fiber diaphragm preparation process: Cut the uncontaminated glass fiber diaphragm into a diameter of 16 mm.

[0089] Preparation process of cellulose filter paper membrane: Cut uncontaminated cellulose filter paper membrane into 16mm diameter.

[0090] Assembling button-type LIR2032 Zn / / Zn symmetrical battery, Zn / / Cu asymmetrical battery, Zn / / AC hybrid capacitor process: first put the spring piece into the negative electrode shell side, then put the gasket, zinc sheet and diaphragm in turn, drip the electrolyte prepared in the above embodiment and comparative example to wet the diaphragm, then put the zinc sheet (symmetrical battery), activated carbon positive electrode sheet (hybrid capacitor), copper positive electrode sheet (half-cell), and positive electrode shell respectively, and then put them into the static press for static pressure sealing, put the assembled battery into a vacuum drying oven (25°C) for 4h, and assemble the Zn / / Zn symmetrical battery, Zn / / AC zinc ion hybrid capacitor and Zn / / Cu asymmetrical battery for standby use. Then carry out the cycle performance test.

[0091] Assembling button-type LIR2032 Cu / / Cu symmetrical battery process: first put the spring piece into the negative electrode shell side, then put the gasket, copper sheet and diaphragm in turn, drip the electrolyte prepared in the above embodiment and comparative example to wet the diaphragm, then put the copper sheet and positive electrode shell, and then put it into the static press for static pressure sealing, put the assembled battery into a vacuum drying oven (25°C) for 4 hours, and then use it. Then use the assembled Cu / / Cu symmetrical battery for cycle performance test.

[0092] 2. Test methods and results

[0093] (1) Scanning electron microscope (SEM) sample preparation: at 25°C, 2 mA cm -2 , 1mAh·cm -2 Under the conditions, the zinc sulfate solutions prepared in the above embodiments and comparative examples were used as electrolytes to assemble Zn / / Zn symmetrical batteries. After cycling for 100 h, the zinc negative electrode samples were taken for SEM test observation.

[0094] SEM test results are as follows Figure 3 As shown, Figure 3 a in the figure is the test result of comparative example 1 (hereinafter, corresponding batteries are referred to as examples 1-3 and comparative example 1), and it can be observed that the dendrites grow in disorder and the interface is not smooth; Figure 3 b and c are the test results of Examples 2 and 3, respectively. It can be observed that the zinc crystals grow flat and dense, which is beneficial to the long cycle process of the battery; Figure 3 d in FIG. 1 is the test result of Example 1. It can be observed that the zinc crystals grow flat and dense, which is beneficial to the long cycle process of the battery.

[0095] (2) The test results of Zn / / Zn symmetrical battery are as follows Figure 4 As shown, the Zn / / Zn symmetric battery of Comparative Example 1 is at 25°C and 2 mA·cm -2 , 1mAh·cm -2 Under these conditions, the cycle life is only 33h ( Figure 4 a); Zn / / Zn symmetric cell using PV and RR color-changing electrolyte at 25°C, 2 mA cm -2 , 1mAh·cm -2 Under these conditions, the cycle life reaches 400h and 831h respectively ( Figure 4 b, c); Zn / / Zn symmetric battery using BCPS color-changing electrolyte at 25°C, 2 mA cm -2 , 1mAh·cm -2 Under these conditions, the cycle life reaches 2000h( Figure 4 d) in.

[0096] (3) The test results of Cu / / Cu symmetric battery are as follows Figure 5 As shown, the Cu / / Cu symmetric battery of Comparative Example 1 is at 25°C and 2 mA·cm -2 , 1mAh·cm -2 Under these conditions, the cycle life is only 56h ( Figure 5 a); Cu / / Cu symmetric cell using BCPS color-changing electrolyte at 25°C, 2 mA cm -2 , 1mAh·cm -2 Under these conditions, the cycle life reaches 590h ( Figure 5 b) in the above.

[0097] (4) Zn / / Cu asymmetric battery at 25°C, 2 mA cm -2 , 1mAh·cm -2 The charge and discharge test under the conditions Figure 6 As shown, the coulombic efficiency of the Zn / / Cu asymmetric battery in comparative example 1 fluctuated violently at 227 cycles, and the coulombic efficiency dropped to 0%; the coulombic efficiency of the Zn / / Cu asymmetric battery using the BCPS color-changing electrolyte remained 100% at 429 cycles.

[0098] (5) CV test results of Zn / / AC zinc ion hybrid capacitors are shown in Figure 7 As shown, the CV curve of comparative example 1 is quasi-rectangular, which is a typical feature of hybrid ion capacitors, but has no additional capacity; the CV test results of the Zn / / AC zinc ion hybrid capacitor using BCPS color-changing electrolyte are shown in Figure 7 As shown in a, the CV curve has a prominent peak, indicating that there is an additional capacity. The CV test results of the Zn / / AC zinc ion hybrid capacitor using PV color-changing electrolyte are shown in Figure 7 As shown in (b), the CV curve has a prominent peak, indicating that there is an additional capacity. The additional redox reaction mechanism of BCPS and PV is as follows Figure 7 As shown in c.

[0099] (6) Zn / / AC zinc ion hybrid capacitor at 1A·g -1 The test results under current density charge and discharge are as follows Figure 8 As shown in Figure 1, the coulombic efficiency of comparative example 1 is close to 100%, but the capacity before cycling is 62.0 mAh g -1 After 1000 cycles, the capacity is 54.6 mAh g -1 , the capacity retention rate is only 88.1%; the coulombic efficiency of the Zn / / AC zinc ion hybrid capacitor using BCPS color-changing electrolyte is 100%, and the capacity before cycling is 69.8 mAh g -1 After 1000 cycles, the capacity is 62.4 mAh g -1, the capacity retention rate is 89.4%.

[0100] In summary, the present invention adopts metal ion indicator to prepare color-changing electrolyte, and its color-changing characteristics can more conveniently characterize the boundary, composition and structure, and after the metal indicator combines with the metal ion, the solvation structure of the metal ion is improved. Fig. 9 The schematic diagram is a schematic diagram of optimizing and regulating the color-changing electrolyte by the metal ion indicator prepared in Examples 1-3, which can reduce the occurrence of electrode side reactions, improve electrode stability, and provide additional capacity for energy storage devices through its reversible redox reaction. Further research can find that the metal ion indicator is suitable for different metal ions, providing a universal optimization strategy for metal electrodes. The present invention has the characteristics of simple process and low cost, which is of great significance to promoting the commercialization of aqueous electrolytes.

[0101] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. An electrolyte containing a metal ion indicator, characterized in that: The metal ion indicator is an organic compound or a salt thereof; the organic compound has a parent core structure and a substituent, the parent core structure is selected from 4-dibenzhydryl-2,5-cyclohexadiene-1-one, phenylazonaphthalene, triazine-phenylazonaphthalene, naphthylazonaphthalene, diphenylbisazonaphthalene, phenylazobenzene, or triphenylmethane; the substituent of the organic compound is selected from at least one of a hydroxyl group, a sulfonic acid group, a carboxyl group, a halogen group, an arsenic acid group, and a dicarboxymethyl nitrogen group.

2. The electrolyte containing a metal ion indicator according to claim 1, characterized in that: When the mother core structure is 4-benzhydryl-2,5-cyclohexadiene-1-one, the metal ion indicator is pyrogallol purple, meta-cresol purple, meta-cresol purple sodium, xylenol orange sodium, methylthymol blue, bromocresol purple, bromocresol purple sodium, bromocresol green or bromocresol green sodium.

3. The electrolyte containing a metal ion indicator according to claim 1, characterized in that: When the parent core structure is phenylazonaphthalene, the metal ion indicator is acidic mordant blue K, 1-(2-pyridylazo)-2-naphthol or chrome blue SE; and / or, when the parent core structure is triazine phenylazonaphthalene, the metal ion indicator is reactive red 2; and / or, when the parent core structure is naphthylazonaphthalene, the metal ion indicator is chrome black T or chrome blue black R; and / or, when the parent core structure is diphenyldisazonaphthalene, the metal ion indicator is azoarsine III; and / or, when the parent core structure is phenylazobenzene, the metal ion indicator is 4-(2-pyridylazo)resorcinol.

4. The electrolyte containing a metal ion indicator according to claim 1, characterized in that: When the parent core structure is triphenylmethane, the metal ion indicator is bromophenol blue, bromophenol blue sodium, bromophenol red, or bromophenol red sodium.

5. The electrolyte containing a metal ion indicator according to any one of claims 1 to 4, characterized in that: The components of the electrolyte include: one or more metal ion indicators, a soluble electrolyte, and water.

6. The electrolyte containing a metal ion indicator according to claim 1, characterized in that: The soluble electrolyte includes at least one of zinc sulfate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, copper sulfate, copper chloride, magnesium chloride, calcium chloride, lithium chloride, sodium chloride, potassium chloride, and potassium hydroxide.

7. The electrolyte containing a metal ion indicator according to claim 1, characterized in that: The total concentration of the metal ion indicator in the electrolyte is 0.01-3000mmol·L -1 .

8. An aqueous electrochemical energy storage device, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte containing a metal ion indicator as claimed in any one of claims 1 to 7.

9. The aqueous electrochemical energy storage device according to claim 8, characterized in that: The positive electrode is a positive electrode current collector loaded with a positive electrode active material; the positive electrode active material is selected from at least one of activated carbon, carbon nanotubes, MXene, manganese-based oxides, vanadium-based oxides, Prussian blue derivatives, polyanion compounds, and organic positive electrode materials; And / or, the negative electrode is at least one of metallic zinc or metallic zinc-modified metal, metallic copper or metallic copper-modified metal, metallic tin or metallic tin-modified metal, metallic magnesium or metallic magnesium-modified metal, metallic calcium or metallic calcium-modified metal, metallic lithium or metallic lithium-modified metal, metallic potassium or metallic potassium-modified metal.

10. Any of the following applications of the aqueous electrochemical energy storage device according to claim 8 or 9: 1) Supercapacitors; 2) Hybrid capacitors; 3) Metal ion batteries; 4) Flow battery.

Citation Information

Patent Citations

  • Cell comprising thermochromic polymer and defect detection method using same

    CN115380420A

  • Application of aromatic micromolecule electrolyte additive

    CN116598606A

  • Secondary battery electrolyte, secondary battery, and vehicle

    CN117638223A

  • Application of dye molecules as additive in preparation of electrolyte

    CN118841644A

  • Electrolyte with indicator

    CN1886851A